2020
DOI: 10.1111/pan.13965
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational trial evaluating factors predictive of accurate endotracheal tube positioning in neonates and small infants

Abstract: Background There is a high incidence of endotracheal tube malposition in neonates and small infants. Yet, verification of accurate endotracheal tube location via radiographic imaging involves radiation exposure. Aims This study aimed to identify demographic and clinical parameters associated with accurate endotracheal tube positioning. Methods We conducted a prospective single‐center study with term and preterm neonates and small infants between January 2018 and November 2019. We investigated correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The gold method for determining the proper depth of tracheal tube is CXR. Other disadvantages of these methods are that they are not always available [ 6 ] and since a proper position is needed for radiography, locating the tube might encounter problem [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gold method for determining the proper depth of tracheal tube is CXR. Other disadvantages of these methods are that they are not always available [ 6 ] and since a proper position is needed for radiography, locating the tube might encounter problem [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They reviewed 186 nasal intubations in 139 patients and found that clinical measures such as experience of the provider, previously known tube position in patients previously intubated, and auscultation were not reliable in predicting correct endotracheal tube positioning in neonates. 4 Without reliability in experience and clinical examination, is proper endotracheal tube positioning solely determined by chest radiography, as Kuhns and Poznanski have suggested? The introduction of pointof-care ultrasound (POCUS) to the neonatal intensive care unit may change the tide once more.…”
mentioning
confidence: 99%